NURSES ON THE FRONTLINE: EVALUATING KNOWLEDGE, ATTITUDE AND PRACTICES IN MANAGING IRON DEFICIENCIES AT A TERTIARY CARE HOSPITAL (Journal of Medical & Health Sciences Review, 2025)
The study examines iron deficiency anemia persists as a fundamental worldwide healthcare problem, mostly within poor regional communities. Nurses exercise essential duties for IDA treatment yet knowledge deficits combined with poor attitudes and practices disturb their ability to provide effective care. The research evaluates nurse IDA management competency at a tertiary care hospital to identify both successful and underdeveloped competencies for future intervention planning. Researchers executed a cross-sectional survey to evaluate nurses in a tertiary care hospital about their IDA management-related KAP. Data analysis revealed which areas nurses needed more knowledge as well as their beliefs about dietary education and cultural competence and practical obstacles to interdisciplinary work. Nurses displayed strong knowledge levels concerning IDA pathophysiology and symptom recognition for both dimensions (51% strongly agreed and 52% strongly agreed respectively). A significant number of nurses reported inadequate understanding of heme and non-heme iron source distinction as well as patient education techniques for iron absorption (64% and 66% respectively). The nurse's lack of cultural dietary habit awareness reached 68% which prevented them from providing tailored care that considers individual cultural backgrounds. All nurses expressed their support for IDA management while endorsing mandatory training as 62% strongly agreed to this requirement. Staff members demonstrated entire confidence in delivering nutritional counseling even though their knowledge levels were insufficient. Nurses demonstrate excellent theoretical understanding alongside positive attitudes about IDA management but lack essential competencies when providing dietary guidance across different cultures. Competency-based training becomes essential because nurses fail to recognise the gap between their self-assessed skills and actual capability levels. Standard educational standards with interdisciplinary collaboration and institutional policy changes will provide nurses with the skills required to deliver evidence-based IDA management that meets cultural needs. To measure the effect of training interventions on patient results researchers should conduct long-term research across several medical facilities.